DISEASES OF THE POPULATION FROM THE LEVEL OF AIR POLLUTION IN REGIONAL CONDITIONS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In recent years the study of the dependence of changes in the health of the population under the influence of environmental factors has become an important object of numerous scientific studies. It is air pollution that causes up to 30% of common diseases. The relationship between the concentrations of atmospheric pollutants and the prevalence of diseases of the respiratory system, cardiovascular system, bronchial asthma is considered proven.